Novel and Alternative Therapeutic Strategies for Controlling Avian Viral Infectious Diseases: Focus on Infectious Bronchitis and Avian Influenza - Abbas, Ghulam; Yu, Jia; Li, Guangxing (Frontiers in Veterinary Science, 2022)
The growth of poultry farming has enabled higher spread of infectious diseases and their pathogens among different kinds of birds, such as avian infectious bronchitis virus (IBV) and avian influenza virus (AIV). IBV and AIV are a potential source of poultry mortality and economic losses. Furthermore, some pathogens have the ability to cause zoonotic diseases and impart human health problems. Antiviral treatments that are used often lead to virus resistance along with the problems of side effects, recurrence, and latency of viruses. Though target hosts are being vaccinated, the constant emergence and re-emergence of strains of these viruses cause disease outbreaks. The pharmaceutical industry is gradually focusing on plant extracts to develop novel herbal drugs to have proper antiviral capabilities. Natural therapeutic agents developed from herbs, essential oils (EO), and distillation processes deliver a rich source of amalgams to discover and produce new antiviral drugs. The mechanisms involved have elaborated how these natural therapeutics agents play a major role during virus entry and replication in the host and cause inhibition of viral pathogenesis. Nanotechnology is one of the advanced techniques that can be very useful in diagnosing and controlling infectious diseases in poultry. In general, this review covers the issue of the poultry industry situation, current infectious diseases, mainly IB and AI control measures and, in addition, the setup of novel therapeutics using plant extracts and the use of nanotechnology information that may help to control these diseases.